(untitled) (Journal of Educational Sciences, 2023)
Inclusive higher education is carried out by teachers, who are a fundamental link in the inclusive environment at the university. At the same time, a review of the literature shows that the problems of inclusive higher education are being implemented partially in Kazakhstan. Therefore, the purpose of this article is a factor analysis of the variables of the Inclusion Index regarding the perception and practical culture of the values and principles of educational inclusion and the current state of inclusive higher education from the standpoint of university faculty. To conduct the study, we provided the online survey and factor analysis of the data obtained by the SPSS 26. This article used personal data ranked according to the Likert scale. The results showed that, in general, university teachers perceive their role in an inclusive environment positively. Nine factors were identified that have the highest loads and account for 63,56% of the variability in the data, which can be distributed as follows: the readiness of faculty to work in an inclusive environment, avoiding stereotypes and supporting diversity at the university, participation of all stakeholders in the university management, inclusion in the university - expanded access and participation, diversity of university students, attitudes towards diversity and inclusiveness, overcoming intolerance towards diversity, cultural barriers in university life, student achievement and the university. As a result, a high degree and unconditional adequacy of factor analysis applicability to the data obtained are revealed. Furthermore, it indicates the reliability of the obtained factor analysis model for assessing the current state of inclusive higher education from university teachers’ viewpoints and articulating further practical actions and research. Key words: inclusive higher education, diversity, university teachers, inclusive environment, factor analysis.